Kadar gula reduksi, protein kasar, dan bahan organik biokonversi kotoran ayam petelur menggunakan kapang Aspergillus niger dan Trichoderma viride sebagai bahan pakan alternatif - Padli, Nadia; Eva Yulia; Ramaiyulis (Fakultas Pertanian Universitas Majalengka, 2024)
Layer manure is generally only used as organic fertilizer, whereas it has the potential as animal feed through bioconversion using Aspergillus niger and Trichoderma viride fungi. The study aims to determine the levels of reducing sugar, crude protein, and organic matter from layer manure resulting from bioconversion with Aspergillus niger and Trichoderma viride. The study used a completely randomized design (CRD) of 4 treatments and four replications. The treatments given were manure inoculated (3% DM) with A: Trichoderma viride (6 days incubation); B Aspergillus niger (6 days incubation); C. Trichoderma viride (3 days incubation) followed by Aspergillus niger (3 days incubation); D. Aspergillus niger (3 days incubation) followed by Trichoderma viride (3 days incubation). The results showed that inoculation of Aspergillus niger and Trichoderma viride in manure bioconversion had a very significant effect (P<0.01) on the levels of reducing sugar, crude protein, and organic matter. The highest levels of reducing sugar were produced in treatment B with Aspergillus niger inoculation. The highest levels of crude protein were produced in treatment A with Trichoderma viride inoculation, and the highest organic matter content was produced through inoculation of a combination of both types of molds. It can be concluded that the manure bioconversion inoculated with Aspergillus niger and Trichoderma viride produced varying levels of reducing sugar, crude protein, and organic matter.